Low peripheral CD34+ stem cells and muscle damage in top-level sportsmen - Bermon, S.; Philip, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Neutropenia and low lymphocytes counts frequently reported in athletes (Bain et al., 2000) can contribute to the increased incidence of upper respiratory tract infections often observed in this population (Nieman, 1995). The purpose of this study was to test whether leucopenia and low haematopoietic stem cell (CD34+) counts, firstly reported at rest in triathletes (Philip and Bermon, 2003), may also occur in other sports, in relation or not with muscle damages. Methods The reversible aspect of such occurrence was tested by using acute exercise as a stress model. White blood cell subsets, CD34+ stem cell counts, and creatine kinase activity (CK) were measured in peripheral blood, at rest, in 25 elite cyclists (age: 28.7 +/- 2.5 (SEM) yrs, weekly training volume: 15.1 +/- 2.1 h/week), 11 professional soccer players (26.3 +/- 2.9 yrs, 15.1 +/- 2.1 h/week), 22 professional water polo players (25.9 +/- 2.1 yrs, 11.5 +/- 0.4 h/week) and 39 sedentary controls (21.0 +/- 0.2 yrs). Then, CD34+ cell and leucocyte counts were measured immediately after a graded and maximal exercise test in all sportsmen and eight controls. Effects of type of sport was tested by one way-ANOVA and Scheffe post-hoc test. Pre-Post exercise differences were tested using paired t test. Results are mean (standard deviation). Results At rest, CD34+ cell counts in cyclists, soccer players, and water polo players were significantly lower than in controls (Table 1). After pooling of haematological data obtained from sportsmen at rest, CD34+ SC counts correlated with leucocyte counts (r = 0.31, P=0.017). No significant correlation was found between CD34+ counts and CK activity at rest in sportsmen. After exercise, athletes exhibited a significant increase for CD34+ cell counts (Table 2). Discussion/Conclusion This original work showed that low CD34+ stem cell counts is a common feature encountered in triathletes and high level cyclists, soccer and water polo players as well. This low CD34+ cell count is linked to leucopenia, but not with the type of training (land vs aquatic, aerobic vs aero-anaerobic). This phenomenon is not linked to index of muscle damage, apparently discarding the hypothesis of a "consumption" of haematopoietic stem cells, for muscle tissue repair (Korbling and Estrov, 2003) purpose after intense sports training. However, mobilisation of CD34+ cell persists after acute physical stress in top-level sportsmen.